On the limitations of closed-loop geothermal systems for electricity generation outside high-geothermal gradient fields - Sri Kalyan Tangirala; Víctor Vilarrasa (Communications Engineering)
Abstract Closed-Loop Geothermal Systems (CLGS) involve connecting the injection and production wells through several borehole-sized parallel laterals instead of circulating a working fluid through a fracture network. Companies have garnered millions of dollars in investments on the claim that CLGS is truly scalable for both heating and electricity generation purposes. We show that high flow rates in the laterals lead to a steep drop in production temperatures because of a rapid cooling of the rock matrix surrounding the wells. Overcoming this physical limitation of CLGS demands an expensive task of drilling several multilaterals to reduce the lateral flow rate. Yet, simulation results indicate that, for a reservoir temperature of 180 °C, the total revenue of these systems fail to recover the lifetime costs incurred, even with 30 multilaterals and a production rate of 75 kg/s, which clearly indicates that CLGS are not scalable for solely electricity generation.